2023
DOI: 10.3389/fnins.2023.1136609
|View full text |Cite
|
Sign up to set email alerts
|

EEG driving fatigue detection based on log-Mel spectrogram and convolutional recurrent neural networks

Abstract: Driver fatigue detection is one of the essential tools to reduce accidents and improve traffic safety. Its main challenge lies in the problem of how to identify the driver's fatigue state accurately. Existing detection methods include yawning and blinking based on facial expressions and physiological signals. Still, lighting and the environment affect the detection results based on facial expressions. In contrast, the electroencephalographic (EEG) signal is a physiological signal that directly responds to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The accuracy of multi-level classification in this study is reported to be above 89%. Gao et al [ 21 ] presented a new model based on a logarithmic spectrogram and convolutional-RNN based on EEG signals. The proposed architecture of these researchers included six convolutional layers with a two-way RNN.…”
Section: Related Workmentioning
confidence: 99%
“…The accuracy of multi-level classification in this study is reported to be above 89%. Gao et al [ 21 ] presented a new model based on a logarithmic spectrogram and convolutional-RNN based on EEG signals. The proposed architecture of these researchers included six convolutional layers with a two-way RNN.…”
Section: Related Workmentioning
confidence: 99%
“…Further, it is seen that there are varied studies which considers hybrid techniques in order to increase the possibilities of accomplishing better accuracies. Hybrid techniques are noted to combine band power of EEG and PERCLOS [26]. Further, spectral power of EEG is combined with ECG [27] while work done in [28] integrates sample entropy, spectral component of EEG, and entropy of ECG.…”
Section: Existing Studies Towards Monitoring Driver's Attentionmentioning
confidence: 99%
“…4 is the downsampling with logarithmic scale of spectrogram (log-spectrogram) was employed, using average pooling and pixel reduction with a 1x6 kernel was intended to reduce the number of initial pixels of the spectrogram to 99x43 pixels as the primary input to the CNN model. This preprocessing method was conducted from previous research and has significant result to make spectrogram feature convertible for small form factor [79][80][81][82][83][84][85].…”
Section: π‘₯(𝜏 πœ”) = ∫ π‘₯(𝑑) πœ”(𝑛 βˆ’ 𝜏) 𝑒mentioning
confidence: 99%